THE EFFECTIVENESS OF TEACHING PERFORMANCE ASSESSMENT (PKG) PROGRAM ONLINE REPORT VIA WEBSITE AT TANGERANG CITY EDUCATION BOARD OF BANTEN PROVINCE (EFEKTIVITAS PELAPORAN PROGRAM PENILAIAN KINERJA GURU (PKG) ONLINE MELALUI WEBSITE PADA DINAS PENDIDI-KAN KOTA TANGERANG PROPINSI BANTEN) - Rohmawati, Tatik (Prodi Teknologi Pendidikan, 2016)
Abstract. This research is aimed to know the report of the effectiveness of Teachers’ Performance Assessment Program (Penilaian Kinerja Guru/PKG) online through web-site www.padamu.siap.web .id on the Education Affairs of Tangeran, Banten Province. Generally, in this implementation, there are many obstacles such as lack of information/promotion relates this program and less of communities’ satisfaction to the managing staff toward the report of the effectiveness of Teachers’ Work Assessment Program through website www.padamu.siap.web .id.This research uses the theory of David Krech, Richard S. Cruthfied and Egerton L. Ballachey. Those theories state that several consid-erable factors to get the effectiveness, there are results’ number, level of satisfactions, creative products and achieved intensity. This research is a descriptive research through qualitative approach. Method of collecting data in this research is interview, observation non participant, literature study and documentation. Then, the considerable technique of information is purposive to the government staff and accidental to the community and school’s staff. The results of this research show that the report of the effectiveness of Teachers’ Work Assessment Program (Penilaian Kinerja Guru/PKG) online through website www.padamu.siap.web .id on the Education Affairs of Tangeran, Banten Prov-ince is not effective enough. It can be seen from the numbers and results which are issued by Educational Affairs considered the effort and nowdays’ achievement. Satisfaction’s level on this program (PKG) is not maximal enough, because many communities and schools are not satisfied to the managing staff of the website. The creative product in this program does not seem good enough. Emotional intensity of the staff in managing web-site www.padamu.siap.web.id is not controlled well.Keywords: Effectiveness, Program Penilian Kinerja Guru Online (Teachers’ Work AssessmentAbstrak. Penelitian ini untuk mengetahui efektivitas pelaporan program penilaian kiner-ja guru (PKG) online melalui website www.padamu.siap.web.id pada Dinas Pendidikan Kota Tangerang Propinsi Banten. Pelaksanaannya masih banyak mengalami berbagai hambatan mulai dari kurangnya sosialisasi pada pelaksanaan program, tingkat kepuasan masyarakat yang belum puas terhadap aparatur pada pelaporan program penilaian kinerja guru online melalui website www.padamu.siap.web.id. Penelitian ini menggunakan teori dari David Krech, Richard S. Cruthfied dan Egerton L. Ballachey. Teori ini. menyebutkan beberapa faktor yang harus diperhitungkan dalam efektivitas yaitu jumlah hasil, tingkat kepuasan yang diperoleh, produk kreatif, intensitas yang akan dicapai. Metode penelitian deskriptif dengan pendekatan kulitatif. Pengumpulan data yang digunakan wawancara, observasi non partisipan, studi kepustakaan dan dokumentasi. Sedangkan teknik penentuan informannya purposive untuk aparatur, accidental untuk masyarakat dan pihak sekolah. Hasil penelitian menunjukkanpenilaian kinerja guru online melalui website www.padamu.siap.web.id, pada Dinas Pen-didikan Kota Tangerang belum efektif dilihat dari jumlah dan hasil yang dikeluarkan Dinas Pendidikan mempertimbangkan usaha dan hasil pencapaian saat ini. Tingkat kepuasan pada program PKG ini belum maksimal karena masih banyak masyarakat dan sekolah yang be-lum puas terhadap kinerja aparatur pengelola website. Produk kreatif pada pelaksanaan pro-gram PKG belum cukup baik. Intensitas emosi aparatur dalam penanganan website www.padamu.siap.web.id belum terkontrol dengan baik.Kata kunci : Efektivitas, Program Penilian Kinerja Guru Online, Website www.padamu.siap.web.id